Epicardial implantation of a leadless pacemaker in a lamb model. Issue 12 (22nd September 2020) - Backhoff, David; Betz, Teresa; Eildermann, Katja; Paul, Thomas; Zenker, Dieter; Bonner, Matthew; Krause, Ulrich
Abstract: Background: Pacemaker used in small children typically consist of an abdominally placed generator and epicardially affixed leads, making such a system prone to lead dysfunction during growth. Aim of this study was to investigate the feasibility of epicardial pacing with a leadless pacemaker in a lamb model. Animals and methods: Seventeen lambs underwent epicardial implantation of a Micra transcatheter pacing system (TPS) (Medtronic, Minneapolis, MN, USA) via left‐lateral thoracotomy to the left ventricle (LV) surface (n = 11/17) and to the left atrial appendage (n = 6). Ventricular devices were fixated with the tines within the pericardium, whereas the tines of the atrial devices penetrated the myocardium of the left atrial appendage. After 31 weeks, animals were sacrificed and hearts were explanted for histological analysis. Results: Following implantation, median P/R amplitude was 4.25/5.5 mV while median pacing threshold was 1.1/1.9 V at 0.24 ms. After 31 weeks, median P/R amplitude was 3.3/4.2 mV. Median atrial pacing threshold was 0.5/0.24 ms. Eight of 10 ventricular pacemakers had lost capture at standard impulse width even at maximum impulse amplitude. On explantation, firm adhesion of the device to the thoracic wall and dislodgement of the electrode tip was found in those ventricular devices. Conclusions: Firm fixation of the Micra electrode to the epicardial surface as applied to the atrial devices resulted in excellent electrical properties during midterm follow up. Pericardial fixation as in the ventricular devices was associated with loss of capture. Therefore, it is important to embed the tines in the myocardium and to choose an alternative implantation site allowing for safe fixation of the Micra TPS in a position perpendicular to ventricular epimyocardium.